Teledentistry in Oral Diagnostic: Unveiled Myths and Challenges to Be Overcome - Livian Isabel de Medeiros Carvalho; Eduarda Gomes Onofre de Araújo; Hélder Domiciano Dantas Martins; Edson Hilan Gomes de Lucena; Paulo Rogério Ferreti Bonan (Association of Support to Oral Health Research (APESB), 2024)
Objective: To reveal the capabilities of the Teleinterconsulting application in Stomatology, shedding light on how this tool operates within our own experience. Material and Methods: This observational and cross-sectional study was carried out using data obtained from the pilot study of the Teleinterconsulta application in Stomatology in Paraíba, Brazil, from April 2021 to October 2023. A descriptive analysis of the data was carried out, including an analysis of the experiences of the situation. Results: This study involved the participation of 22 dentists who acted as consultants in the application, which already has more than 400 registered dentists who participate in the healthcare network. Conclusion: Teleconsultation in Stomatology can be a powerful tool that can contribute to the early diagnosis of potentially malignant diseases. We anticipate that this brief communication will inspire professionals to adopt and integrate technologies that allow teleconsultation, promoting greater openness to e-health practices.